Americans' Use of Time, 1965-1966 - Converse, Philip E. ([Verlag nicht ermittelbar], 1984)
These data were gathered as part of a multinational time budget project (see also TIME USE IN ECONOMIC AND SOCIAL ACCOUNTS, 1975-1976 [ICPSR 7580] and AMERICANS' USE OF TIME, 1965-1966, AND TIME USE IN ECONOMIC AND SOCIAL ACCOUNTS, 1975-1976: MERGED DATA [ICPSR 7796]). This study includes variables of two general types. One group concerns sociodemographic characteristics of respondents and households, the other set deals with time use. The time use data were obtained by having respondents keep a complete diary of their activities for a single 24-hour period between November 15 and December 15, 1965, or between March 7 and April 29, 1966. Additional data were gathered from an interview taken on the day after the diary was completed. Data on both primary and secondary time use were recorded, along with where and with whom the activities took place.